Employee Stock Ownership vs. Profit Sharing - Rick Harbaugh (Claremont McKenna College, Department of Economics, 2000)
The idea that profit sharing increases employment has been widely tested, but the theoretical basis for the claim is weak and the empirical results are ambiguous. This paper shows that employee stock ownership based on individually-held stakes avoids the problems of traditional profit sharing. Employee stock ownership shifts employment to the efficient level by either raising employment from an initial state of underemployment or decreasing it from an initial state of overemployment. Since the effect on employment is not unidirectional, empirical tests need to differentiate between traditional profit sharing and employee stock ownership and to condition on the initial state of employment.
Keywords: J33; J51; J54; P13; 330; profit sharing; employee ownership; ESOPs; collective bargaining